Evaluasi Supplier Kawat Ulir di CV. Jaya Koil dengan Metode Max-Min - Sebastian, Edwin; Widyadana, I Gede Agus (Jurnal Titra, 2015)
A Firm occasionaly has more than one supplier to fulfill their raw material needs. It happened because the firm is confused in choosing the good and the bad one. Supplier evaluation is conducted to figure it out. This evaluation is based on each supplier performance. The purpose of this reserach is to find out the suppliers performance at CV. Jaya Koil. The method used in this research is max-min method. The result of this research is that thereâs no dominant difference between one supplier with others, so company may allocate its budget on any supplier